Yarns from the desert: sustainable guanaco management - Lichtenstein, Gabriela (2016)
As with most wild ungulates, guanacos compete for pasture with domestic livestock. In Southern Patagonia, Argentina, conflict between guanaco conservation and sheep rearing has increased in recent years due to severe droughts and increased desertification. Ranchers hope to declare guanacos as a ‘pest species’ and are starting culling programmes. But a group of pastoralists living in a protected area have taken a different approach, thereby successfully combining live guanaco management with economic empowerment.